PENGARUH INOVASI PRODUK DAN HARGA TERHADAP NIAT BELI SAMSUNGGALAXY S6(STUDI PADA PENGUNJUNG PLAZA MARINA) - NURKHASAN, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2016)
Abstract Technology development in Indonesia is always develop particularly technology in the communication sector, such as internet and handphone. Now, from the side of handphone have been developed whose name is smartphone technology that far exceed the consument expectation. Samsung Galaxy S6 is the one of smartphone with the most beautiful design and the best, and with the best performance along the Samsung’s history. This research have purposed to analisys and study the influence of product innovation and price on purchase intention of Samsung Galaxy S6 by using multiple regression analisys method. This research was using sample of 110 respondents, they are the Marina Plaza visitors age 18-34 , understand the price of Samsung Galaxy S6, used before smartphone Samsung and has visited minimum the two outlets Samsung. The research result indicated that found influence significantly among product innovation and price on purchase intention of Samsung Galaxy S6 as big as 44,4%, whereas the remainder 55,6% was influenced by other variable in the out of research. Keywords: Product Inovation, Price, Purchase Intention<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />